An assessment and correlation of emotional Intelligence and mental health of medical students - Khan, Huma; Gupta, Rakshit; Mishra, Saurabh (Indian Journal of Community Health, 2022)
Introduction: Emotions like joy, anger, grief, jealousy, love, fear make our life worthwhile. Whatever we do, incites some emotion in us. If we are able to enjoy our emotions, without them having excessive control over us, then we can make ours as well as others’ lives better. Aim of the study was to assess and correlate emotional Intelligence with mental health. Methods: Type of study: Descriptive type of cross sectional study. Sampling: Simple random sampling. Study population: Under graduate students in a private medical college in western Uttar Pradesh. Study duration: 1/07/2019 to 1/09/2019. Sample size: 246. Results: The average emotional intelligence score was 26.82 with standard deviation of ±5.80. Average emotional intelligence among males was 27.04(±6.72) and was 26.63(±5.07) among females. Spearman Rank correlation coefficient “r” =0.789, showed highly positive correlation between ranks from both the score. (p=0.0000). Conclusions: The medical students showing higher scores of emotional intelligence are less likely to be mentally stressed.